The effect of diet and aerobic exercise on Premenstrual Syndrome: Randomized controlled trial - YILMAZ-AKYUZ, Elvan; AYDIN-KARTAL, Yasemin (Revista de Nutrição, 2023)
Objective This study was conducted to determine the effectiveness of aerobic exercise and diet in female students with Premenstrual Syndrome Scale who were studying at the public university. Methods This randomized controlled trial was conducted in a public university in 2018. The population of the study was composed of all female fi rst graders (N=426). The female students were followed-up for two cycles, premenstrual syndrome scale was administered to the students and premenstrual syndrome was found in 43.8% (n=187). However, 106 female students were included in the study divided in three groups (diet, aerobic exercise, control). The diet and aerobic exercise were administered during the three months. Results There was no signifi cant difference in premenstrual syndrome scale mean scores between the post-intervention groups. However, the mean premenstrual syndrome score of the diet and aerobic exercise groups decreased signifi cantly after the intervention. There was a signifi cant difference in visual analogue scale score between the groups after intervention. Besides the students in exercise and diet groups experienced less dysmenorrhea intensity than the control group. Conclusion It was found that diet and aerobic exercise were effective in reducing the symptoms of premenstrual syndrome and dysmenorrhea intensity in female students with premenstrual syndrome.